Association of C(-1019)G with Risk of Development of Major Depression in Diabetics with Respect to Various Pakistani Ethnicities - Tayba Saleha Hashmi, Aqsa Tazarrat, Sadia Muzafar, Sidra Ashfaq, Iqra Anwar, Nafeesa Kiran (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine whether the ethnicity is associated with the risk of development of Major Depressive Disorder (MDD) in adult diabetic population with respect to the genetic association with single nucleotide polymorphism (SNP) C(-1019)G. Material and Methods: A total of 400 subjects were included in the study, out of which 200 were cases and 200 were age, gender and ethnicity matched healthy controls. Out of 200 cases , 100 cases had diabetes mellitus (DM) only and 100 cases had DM with MDD. Both males and females were included in the study having ages 25 years and above. Cases of both type I and type II DM were included in the study. Blood samples were collected and DNA was extracted by Chelax method. Real-time PCR was carried out to determine respective allelic frequencies of C(-1019)G genotype using TaqMan SNP genotyping assays and master mix. Results: According to our results no significant association was found between C(-1019)G genotype and risk of development of MDD in Pakistani diabetic population with respect to Ethnicity but diseased genotype was found more in Pathan population. Conclusion: There is no significant association of SNP C(-1019)G of 5-Hydroxytryptamine 1A receptor gene with MDD in Pakistani diabetics with respect to ethnicity. Keywords: Diabetes mellitus, major depressive disorder, 5-hydroxytryptamine 1A receptor gene, single nucleotide polymorphism, polymerase chain reaction.